Critical success criteria for public-private partnership projects: international experts' opinion. Issue 1 (2nd January 2017) - Osei-Kyei, Robert; Chan, Albert P. C.; Javed, Arshad Ali; Ameyaw, Ernest Effah
ABSTRACT: Public-Private Partnership (PPP) projects success is the ultimate goal of practitioners and government organizations. In this regard, the last decade has seen considerable research into the critical success factors (CSFs) for PPP projects. However, a very important subject which has received very little attention in the normative literature is the success criteria for PPP projects. This paper examines the general perception of purposively sampled international PPP experts on a set of 15 PPP projects success criteria derived from literature. The survey results show that all the success criteria are critical; however seven are very critical. These include: effective risk management; meeting output specifications; reliable and quality service operations; adherence to time; satisfying the need for public facility/service; long-term relationship and partnership; and profitability. The findings of this study are impactful because they inform practitioners on the key measures to consider when evaluating the success of PPP projects. More research should be conducted to further develop a composite success index that could be used to objectively assess the success levels of different PPP projects. In addition, the perceptions of different stakeholders on PPP projects success criteria and the causal relationship between CSFs and success criteria for PPP projects should be investigated.